Adaptive behavior satisfaction index analysis framework for energy efficient building assessment - Keyvanfar, Ali (2013)
Currently, sustainability is one subject that requires attention and application among the stakeholders of any nation. Many techniques for managing sustainability including =sustainable building assessment‘ frameworks have been developed globally. However, the measures within these frameworks have not yet taken into consideration user‘s satisfaction from adaptive behavior in energy efficient indoor environment. Thus, the aim of this study was to develop the adaptive behavior satisfaction index analysis framework for assessing energy efficiency of buildings. Six objectives were identified to achieve this aim, through progress of five research phases and fifteen research steps. First, the study investigated the effect of building users‘ satisfaction from adaptive behavior on energy consumption. On the basis of literature review, a field survey of ten energy efficient office units, and subsequently expert input was conducted. The findings of first objective showed user satisfaction from adaptive behavior had effect on building energy consumption with regards to lighting and cooling. Second objective was to identify and establish building users‘ adaptive behavior in energy efficient indoor environment. In parallel, third objective was to identify and establish energy efficient building assessment characteristics. The fourth objective was to identify and establish, a suitable, user‘s satisfaction index analysis framework. To address second, third, and fourth objectives, literature review and expert input was conducted. Based on the findings, thirty six adaptive behaviors, three main characteristics of assessment framework, and Kano model was selected in the framework development. Aforementioned findings helped in the framework development, thus fulfilling the fifth objective. The adaptive behavior satisfaction index analysis framework was developed in a synectics session including professionals in the relevant field. Furthermore, a preliminary feasibility validation was conducted through users‘ input. The sixth objective, the feasibility of adaptive behavior satisfaction index analysis framework, was validated in a green certified building as the case study. In conclusion, the study successfully developed the aimed ABSI analysis framework. The final framework will be recommended as a design decision support tool for architects practicing energy efficiency.